2018
DOI: 10.4236/ojf.2018.82016
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Homegarden Agrobiodiversity, Practices of Homegardening and Its Role for <i>In-Situ</i> Conservation of Plant Biodiversity in Eastern Hararghe, Kombolcha Town Oromia Regional State Ethiopia

Abstract: Homegarden plays a vital role for the livelihood of the people living in town. Homegarden agrobiodiversity was studied to highlight homegarden frequency, types, plant species, growth form and associated indigenous knowledge. The research was conducted during January to April 2017. A total of 180 randomly selected households were included in the survey. Ethnobotanical data were collected from purposively selected 60 homegardens using observations and semi-structured interviews while markets survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…R. chalepensis belongs to the family Rutaceae and it is used as spices for Tea, Coffee, Shiro Wot, and Mitmit. This result was in line with that of Semu (2018) who reported that R. chalepensis is used as a spice for Coffee and Berbere processing in Hararghe, Kombolcha Town, Oromia of Ethiopia.…”
Section: Spice Plants In the Homegadensupporting
confidence: 92%
See 1 more Smart Citation
“…R. chalepensis belongs to the family Rutaceae and it is used as spices for Tea, Coffee, Shiro Wot, and Mitmit. This result was in line with that of Semu (2018) who reported that R. chalepensis is used as a spice for Coffee and Berbere processing in Hararghe, Kombolcha Town, Oromia of Ethiopia.…”
Section: Spice Plants In the Homegadensupporting
confidence: 92%
“…The diversity of homegarden plants varies from place to place (Kumar and Tiwari, 2017). For instance, 69 species belonging to 40 families from 48 homegardens (Mekonnen et al, 2014) in Jabithenan District, North-Western Ethiopia; 78 species belonging to 35 families from 18 homegardens (Semu, 2018) in Eastern Hararghe, Kombolcha Town Oromia of Ethiopia were recorded. Similarly, 62 plant species of 35 families were recorded in Misha Woreda, Hadiya Zone of the Southern Ethiopia (Woldemichael et al, 2018); 112 plant species classified into 43 families were documented from 75 homegardens in Holeta Town, Oromia of Ethiopia (Amberber et al, 2014) and 20 plant species are documented in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the index represents the probability that two individuals randomly selected from a sample belong to different species. Simpson's index of diversity is subtracted from Simpson's diversity indices (D) by one (Semu, 2018) and mathematically represented as follows:…”
Section: Simpson's Index Of Diversity 1-dmentioning
confidence: 99%
“…Domestication of assorted wild plant species square measure in a home garden that has contributed to extending diversity and supporting livelihoods. Homegardens may be front garden, backyard garden, sideyard garden, both-side garden (Semu, 2018). Home gardens are farm-based and common Agroforestry practices in Nepal (Regmi, 2003).…”
Section: Status Of Home Gardenmentioning
confidence: 99%